RGB Colors and Ecological Optics - Koenderink, Jan; van Doorn, Andrea; Gegenfurtner, Karl (Frontiers in Computer Science, 2021)
Object color space is highly structured due to optical constraints (radiant power non-negative, reflectance factors between zero and unity) and ecological context (daylight illuminant). In this setting trichromacy induces a natural geometry through a unique spectral tripartition. Different from null-context colorimetry, one gains two desirable relations: The colorimetric coordinates are coarse-grained spectral reflectance factors and there is a direct link to color experiences, since RGB--coordinates provide ostensive definitions. The framework allows one to deal with subtractive color mixture, source variation, effects of metamerism and relations between scenes and image data in a unified, structured manner.In ecological contexts, colors are effectively object properties. The formal framework is linear algebra and convex geometry. Applications in human~biology, computer graphics, design, etc., are immediate.